Heterojunction modification for highly efficient organic-inorganic perovskite solar cells. - Wojciechowski, K; Stranks, S; Abate, A; Sadoughi, G; Sadhanala, A; Kopidakis, N; Rumbles, G; Li, C; Friend, R; Jen, A; Snaith, H (American Chemical Society, 2014)
Organic-inorganic perovskites, such as CH3NH3PbX3 (X = I, Br, Cl), have emerged as attractive absorber materials for the fabrication of low cost high efficiency solar cells. Over the last 3 years, there has been an exceptional rise in power conversion efficiencies (PCEs), demonstrating the outstanding potential of these perovskite materials. However, in most device architectures, including the simplest thin-film planar structure, a current-voltage response displays an "anomalous hysteresis", whereby the power output of the cell varies with measurement time, direction and light exposure or bias history. Here we provide insight into the physical processes occurring at the interface between the n-type charge collection layer and the perovskite absorber. Through spectroscopic measurements, we find that electron transfer from the perovskite to the TiO2 in the standard planar junction cells is very slow. By modifying the n-type contact with a self-assembled fullerene monolayer, electron transfer is "switched on", and both the n-type and p-type heterojunctions with the perovskite are active in driving the photovoltaic operation. The fullerene-modified devices achieve up to 17.3% power conversion efficiency with significantly reduced hysteresis, and stabilized power output reaching 15.7% in the planar p-i-n heterojunction solar cells measured under simulated AM 1.5 sunlight.